Question and answer
Solve for x: x^2 + 11x + 24 = 0
x^2 + 11x + 24 = 0 (x + 3)(x + 8) = 0; x + 3 = 0; x = -3; x + 8 = 0; x = -8 x = {-3, -8}
Question
Asked 12/18/2010 6:34:10 PM
Updated 4/5/2015 7:05:34 AM
1 Answer/Comment
Get an answer
New answers
Rating
3
x^2 + 11x + 24 = 0

(x + 3)(x + 8) = 0;

x + 3 = 0; x = -3;
x + 8 = 0; x = -8

x = {-3, -8}
Added 4/5/2015 7:05:34 AM
This answer has been confirmed as correct and helpful.
Confirmed by Andrew. [4/5/2015 12:53:24 PM]
Comments

There are no comments.

Add an answer or comment
Log in or sign up first.
Questions asked by the same visitor
Working with polynomials: (2x4 + 3)(4x³+ 2)
Weegy: (2x4 + 3)(4x³+ 2) = 8x^12 + 4x^4 + 12x^3 + 6 (More)
Question
Expert Answered
Updated 7/16/2014 11:07:55 AM
1 Answer/Comment
(2x^4 + 3)(4x^3 + 2) = 8x^7 + 4x^4 + 12x^3 + 6
Added 7/16/2014 11:07:54 AM
This answer has been confirmed as correct and helpful.
Working with polynomial: (12y³ + 8 y² + 20y) / 2y
Weegy: x+2y+z --> x = -2y-z (More)
Question
Expert Answered
Updated 7/16/2014 11:09:47 AM
1 Answer/Comment
(12y³ + 8y² + 20y) / (2y)
= (12y³/2y) + (8y²/2y) + (20y/2y)
= 6y^2 + 4y + 10
Added 7/16/2014 11:09:46 AM
This answer has been confirmed as correct and helpful.
Working with polynomial: (5x – 3.6) – (4x + 1.2)
Weegy: x-4.8 User: Please show the steps on how you got this answer. Thanks (More)
Question
Expert Answered
Updated 7/3/2014 1:57:21 PM
1 Answer/Comment
(5x – 3.6) – (4x + 1.2)

= 5x - 3.6 - 4x - 1.2

= 5x - 4x - 3.6 - 1.2

= x - 4.8
Added 7/3/2014 1:57:21 PM
This answer has been confirmed as correct and helpful.
Confirmed by yumdrea [7/3/2014 2:07:02 PM]
Working with polynomial: (3x^2 + 3x) + (4x + 4). Please show the steps on how you got your answer. Thanks!
Question
Not Answered
Updated 8/10/2014 5:55:48 PM
1 Answer/Comment
(3x^2 + 3x) + (4x + 4)

= 3x^2 + 3x + 4x + 4;

= 3x^2 + 7x + 4
Added 8/10/2014 5:55:48 PM
This answer has been confirmed as correct and helpful.
Confirmed by andrewpallarca [8/10/2014 5:57:18 PM]
Working with polynomial: (6x^2 - 25x - 10) / (3x + 2)
Question
Not Answered
Updated 7/27/2014 12:19:20 PM
1 Answer/Comment
(6x^2 - 25x - 10) / (3x + 2)
= (6x^2/3x+2) - (25x/3x+2) - (10/3x+2)
= 2x - 29/3 R. 28/3
Added 7/27/2014 12:19:20 PM
This answer has been confirmed as correct and helpful.
27,531,536
questions answered
GET
Answers.
GET THE APP.
weegy*
*
Get answers from Weegy and a team of really smart live experts.
Popular Conversations
What is command staff?
Weegy: COMMAND is The act of directing and/or controlling resources by virtue of explicit legal, agency, or delegated ...
10/13/2018 3:32:13 AM| 4 Answers
Simplify this expression: 4p + 9 + (–7p) + 2 A. 3p + 7 B. ...
Weegy: 4p + 9 + ( 7p) + 2 User: Given the formula D = ABC, what is the formula for C? A. C = AD ÷ C B. C ...
10/14/2018 11:12:06 AM| 4 Answers
The Dutch were the only Europeans allowed to trade with Japan as long ...
Weegy: The Dutch were the only Europeans allowed to trade with Japan as long as they gave up all show of [ ...
10/13/2018 8:08:05 PM| 2 Answers
S
R
L
R
P
R
P
R
R
R
R
P
R
Points 601 [Total 1982] Ratings 8 Comments 521 Invitations 0 Online
S
L
P
P
P
Points 541 [Total 1780] Ratings 0 Comments 541 Invitations 0 Offline
S
L
R
P
R
P
R
P
R
P
R
Points 540 [Total 1767] Ratings 8 Comments 460 Invitations 0 Offline
S
L
R
Points 420 [Total 635] Ratings 1 Comments 410 Invitations 0 Online
S
Points 53 [Total 53] Ratings 0 Comments 53 Invitations 0 Offline
S
Points 20 [Total 20] Ratings 0 Comments 0 Invitations 2 Offline
S
Points 10 [Total 10] Ratings 1 Comments 0 Invitations 0 Offline
S
Points 10 [Total 10] Ratings 0 Comments 0 Invitations 1 Offline
S
Points 10 [Total 10] Ratings 0 Comments 0 Invitations 1 Offline
S
L
L
Points 10 [Total 5274] Ratings 0 Comments 0 Invitations 1 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.